The investigation of the relationship between perceived freedom and brief resilience: The role of participation in physical activity - TÜLAY AVCI TAŞKIRAN; BÜLENT GÜRBÜZ (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2021)
Background: This study was designed to examine the relationship between perceived freedom in leisure and psychological resilience of university staff. Material and Methods: The sample group of the study was composed of 189 academic and 81 administrative university staff (Mage=36.11±7.34). Participants were assessed based on the "Perceived Freedom in Leisure Scale (T-PFLS)" and the "Brief Resilience Scale (T-BRS)". ANOVA, independent samples t-test, and Pearson correlation analysis methods were used to analyze the data. Results: T-test analysis indicated that there was no significant difference between the mean scores of "T-PFLS"; however, there was a statistically significant difference between the mean scores of "T-BRS" with regard to gender. The male participants' mean scores were higher than those of the female participants. The analysis revealed statistically significant differences in "T-PFLS" and "T-BRS" mean scores with respect to the position at the university. ANOVA analysis indicated statistically significant differences in mean scores of "T-PFLS" and "T-BRS" with respect to leisure participation preference. The mean scores of frequent participants were higher than the others in both of the scales. There was a statistically significant positive and moderate correlation between the mean scores of "T-PFLS" and "T-BRS" scores. Conclusion: As a result, active participants reported higher perceived freedom and psychological resilience scores.